PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) PADA PERTUMBUHAN BIBIT KELAPA SAWIT (ElaeisguineensisJacq) DI MAIN-NURSERY PADA MEDIUM SUBSOIL ULTISOL - Bariyanto '; Nelvia '; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Plant oil palm is the dominant plantation crops cultivated in Riau. Needs of oil palm seedlings increased with the expansion of the land and replanting. This research aims to study the application compost of oil palm empty fruit bunches(OPEFB) in the growth of oil palm seedlings in the nursery main- medium ultisol subsoil. This research was conducted in the greenhouse agriculture university faculty Riau, from September to December 2013. The study was carried out experiments using a completely randomized design ( CRD ), which consists of 4 treatments each ( 0 , 20 , 30 , and 40 tons of compost of OPEFB/ha ), each repoted 4 times. The results showed that application of compost of oil palm empty fruit bunches at a dose of 30 tones/ha can increase seedling height and diameter weeviloil palm are greater than the without compost and aplication 20 tons compost of OPEFB /ha. The increase of dose compost of OPEFB to 40 tons/ha increased seedling height and weevil diameter greates. Keyword: Palm oil, Ultisols and Oil Palm Empty Fruit Bunch.